Young man in a hurry : a memoir of discovery [compact disc, unabridged] - Newsom, Gavin, 1967- (Penguin Random House, 2026)
California Governor Gavin Newsom reflects on the long personal journey that has shaped him, sharing a California story of identity, belonging, and the defining moments that inspired his life in politics.